A STRUCTURAL AND MYTHOLOGICAL COMPARISON OF TURKIС EPIC OGUZNAME AND IRISH EPIC TÁIN BÓ CÚAILNGE (SCIENCE TIME JOURNAL, 2026)
This study compares the Oguz Khagan Epic and the Tain Bo Cuailnge, analyzing their structures and mythologies. Using Propp, Campbell, and Levi-Strauss, it explores patterns of heroism, social organization, and cosmology within distinct oral traditions.